Effect of Multimedia Instructional Approach on English Writing Performance of Pre-Service Technical Teachers in South-Western Nigeria - Cyril Abioye Charles Olowoyeye; Oladuni Olufunso Deji-Afuye; Gboyega Ayodeji Aladesusi (Indonesian Journal of Multidiciplinary Research, 2023)
This study examined the Effect of the Multimedia Instructional Approach (MIA) on the English writing performance of pre-service Technical teachers in Southwestern Nigeria. The study adopted a quasi-experimental design of the pre-test post-test non-equivalent control group design to compare the performance of students. The following research instruments were adopted for the study: English Writing Performance Tests (EWPT) set A and B as well as Multimedia Instructional Software Package. Mean, standard deviation, and analysis of covariance (ANCOVA) were used for data analysis. The findings of the study revealed that MIA, was effective for teaching English language writing and there is no significant difference between males and females in the English writing performance of the pre-service technical teachers taught through MIA. This study concluded that MIA for English writing is an important variable because it better predicts students’ writing performance in the English Language than the conventional method of teaching. The study, therefore, recommended that teachers of the English language should deploy the use of multimedia technology for instructional delivery in the classroom as it better predicts the students’ academic performance.